2021
DOI: 10.1158/2326-6066.cir-20-0203
|View full text |Cite
|
Sign up to set email alerts
|

Sialylation of CD55 by ST3GAL1 Facilitates Immune Evasion in Cancer

Abstract: Altered glycosylations, which are associated with expression and activities of glycosyltransferases, can dramatically affect the function of glycoproteins and modify the behavior of tumor cells. ST3GAL1 is a sialyltransferase that adds sialic acid to core 1 glycans, thereby terminating glycan chain extension. In breast carcinomas, overexpression of ST3GAL1 promotes tumorigenesis and correlates with increased tumor grade. In pursuing the role of ST3GAL1 in breast cancer using ST3GAL1-siRNA to knockdown ST3GAL1,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…( 25 , 26 ) We have recently reported that mAbVK9 can mediate CDC. ( 27 ) The finding from this study also indicates that VK9 could induce ADCC against the Globo H–expressing cancer cell line. Moreover, we observed increased NK cells and significant up‐regulation of several NK cell markers in the ICC tumor microenvironment of mAbVK9 treated rats.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…( 25 , 26 ) We have recently reported that mAbVK9 can mediate CDC. ( 27 ) The finding from this study also indicates that VK9 could induce ADCC against the Globo H–expressing cancer cell line. Moreover, we observed increased NK cells and significant up‐regulation of several NK cell markers in the ICC tumor microenvironment of mAbVK9 treated rats.…”
Section: Discussionsupporting
confidence: 64%
“…( 25 , 26 ) We have recently reported that mAbVK9 can mediate CDC. ( 27 ) As shown in Supporting Fig. S2 , mAbVK9 induced significant ADCC of GHCer‐pretreated HuCCT1 cells with a mean percent lysis of 42.45% ± 5.1%, as compared with the isotype control of 9.79% ± 3.4% at the E:T ratio of 12.5:1 ( P < 0.05).…”
Section: Resultsmentioning
confidence: 67%
“…Most infected patients were males (n = 91, 91%). The median age [interquartile range (IQR)] of patients with severe COVID-19 disease defined by admission to ICU (47 years), but not mild-moderate patients, was higher than the control groups (vs. 38 [33][34][35][36][37][38][39][40][41][42] years, p < 0.001). The ethnicity distribution in the severe and mild-moderate groups was not significantly different; however, the control group had a higher percentage of the Indian subcontinent ethnicity (p = 0.04).…”
Section: Study Cohort Characteristicsmentioning
confidence: 96%
“…Consistently, inhibition of ST3GAL1 has been proposed as a strategy to block CD55-mediated immune evasion. Mechanistically, authors showed that O-linked desialylation of CD55 by ST3GAL1 silencing results in increased C3 deposition and complement-mediated lysis of breast cancer cells, enhancing sensitivity to antibody-dependent cell-mediated cytotoxicity [ 92 ]. A recent work showed that circulating monocytes that infiltrate the tumor can interact with tumor-derived sialylated structures through the receptors Siglec-7 and Siglec-9 in pancreatic ductal adenocarcinoma.…”
Section: Roles Of Sialyltransferases In Cancermentioning
confidence: 99%